Hazard analysis critical control points in coleslaw production, storage and retail sale - Tongol, Maria Jenina A.; Azanza, Ma. Patricia V. (1997.)
A great number of microbiological hazards and risks have been identified with the preparation and storage of chilled foods in food service establishments. Outbreaks of foodborne diseases have been associated with mishandling of these types of foods. For this study, microbial hazards associated with coleslaw were evaluated using the Hazard Analysis Critical Control Points (HACCP) system. This study was conducted for the purpose of presenting a detailed approach for the implementation of a HACCP program in coleslaw production, storage and retail sale. The food flow of coleslaw production, storage and retail sale was established based on the recipe used in the store, observations of actual production and interviews among the store personnel. The microbial hazards in the steps were identified and their severity assessed by quantifying the concentrations of the indicator microorganisms at each step. Coleslaw preparation steps included the washing of cabbage and carrots; sanitizing of cabbage; slicing of vegetables; mixing of the sliced vegetables with dressing and pineapple tidbits; storage of prepared coleslaw at chiller temperatures; and retail sale of the coleslaw. The microbial analyses included aerobic mesophilic plate count, aerobic psychrophilic plate count, coliform count and yeast and molds count. Average mesophilic plate count of the coleslaw produced from the original procedure was 5.0 x 10^6 cfu/g, average psychrophilic plate count was 5.0 x 10^5 cfu/g, average coliform count was 5.0 x 10^3 cfu/g and yeast and mold count was 4.0 x 10^4 cfu/g. The microbial hazards in the production were identified based on the results of the microbial analysis. Corrective measures were implemented to improve the microbial safety of the coleslaw produced. A revised procedure which includes the corrective measures for coleslaw production was drafted and implemented. The critical control points (CCPs) in the revised procedure were identified. The CCPs were proper washing of the vegetables; pH and microbial quality of the coleslaw dressing and pineapple tidbits; proper sanitizer concentration and contact time; pH of the fresh coleslaw; time and temperature conditions of the coleslaw during storage and display. The efficacy of this procedure was assessed by means of microbial evaluation. The tests used were similar to those used to identify hazards in the original procedure. Microbial evaluation showed that the mesophilic plate count of the coleslaw produced from the revised procedure was 9.1 x 10^4 cfu/g; psychrophilic plate count was 7.9 x 10^3 cfu/g, coliform count was 2.2 x 10^2 cfu/g and yeast and mold count was 4.6 x 10^2 cfu/g. These results proved that the revised procedure may be recommended for implementation. This paper may be used as a guide for the implementation of a HACCP program to products similar in preparation and storage to coleslaw.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Salad vegetables; Food handling